THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT ROLE ON THE PERFORMANCE OF EMPLOYEES AT PT BANK SUMUT KRAKATAU MEDAN CITY BRANCH OFFICE - Dongoran, Sapina; Harahap, Muhammad Ikhsan (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
Roles can be defined as unique behaviors that represent the characteristics of each individual in a work group or social environment that has a major influence on events. In terms of improving the quality of performance of Krakatau North Sumatra branch office, this will be achieved through continuous improvement of the quality of human resources, who always strive to improve the level and quality of services to meet the needs and expectations of the community. The purpose of this study was to determine the influence of management on the quality of employee performance at PT Bank Sumut in Krakatau Medan City Branch Office. The sample used is a saturation sample, taking all members of the population as a sample of 13 employees. The data collection method used is interviews, the role of HR management in employee performance indicators is found through a literature study, the indicators used include work systems and structures, work quality, collaboration creativity. The results of the study indicate that (1) HR management has a significant effect on the quality of the performance of PT Bank Sumut Krakatau Medan City Branch Office; (2) work quality has a significant effect on the quality of employee performance at PT Bank Sumut Krakatau Medan City Branch Office; while (3) obstacles or constraints has simultaneously affected the quality of employee performance at PT Bank Sumut Krakatau Medan City Branch Office.